CRYOPRESERVED MESENCHYMAL STEM CELLS IMPACT ON THE SPINAL CORD TISSUE IN RATS WITH EXPERIMENTAL ALLERGIC ENCEPHALOMYELITIS - Semenova, V.M.; Tsymbalyuk, V.I.; Liubich, L.D.; Egorova, D.M.; Stayno, L.P.; Verbovska, S.A.; Slynko, E.I.; Pichkur, L.D. (World of Medicine and Biology, 2020)
Mesenchymal stem cells from human umbilical cord (1×106) are able to correct neurodegenerative changes in the spinal cord of rats with chronic experimental allergic encephalomyelitis under the suboccipital administration. Cells cryopreserved in solution with 3 % dimethyl sulfoxide, 15 % ethylene glycol, 10 % sucrose, 12 % trehalose, 60 % fetal calf serum, slow the build-up of pathological changes at day 35; cryopreserved in solution with 4 % dimethyl sulfoxide, 6 % trehalose, 90 % fetal calf serum, – at days 35–60; cryopreserved in solution with 10 % dimethyl sulfoxide, 90 % fetal calf serum, – have no effect. Selection of optimal cryoprotectants to save the biological properties of these cells and working out the modes and ways of their administration remains relevant.